2023
DOI: 10.3389/frobt.2023.1086798
|View full text |Cite
|
Sign up to set email alerts
|

An embarrassingly simple approach for visual navigation of forest environments

Abstract: Navigation in forest environments is a challenging and open problem in the area of field robotics. Rovers in forest environments are required to infer the traversability of a priori unknown terrains, comprising a number of different types of compliant and rigid obstacles, under varying lighting and weather conditions. The challenges are further compounded for inexpensive small-sized (portable) rovers. While such rovers may be useful for collaboratively monitoring large tracts of forests as a swarm, with low en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Workaround solutions have been, at times, used to circumvent the lack of depth information in camera images. For instance, recently, Niu et al [190] proposed a low-cost navigation system tailored for small-sized forest rovers, including a lightweight CNN, to estimate depth images from RGB input images from a low-viewpoint monocular camera. The depth prediction model proposed in this research is designed to infer depth information from low-resolution RGB images using an autoencoder architecture.…”
Section: Spatial Representations In 3d and Depth Completion Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Workaround solutions have been, at times, used to circumvent the lack of depth information in camera images. For instance, recently, Niu et al [190] proposed a low-cost navigation system tailored for small-sized forest rovers, including a lightweight CNN, to estimate depth images from RGB input images from a low-viewpoint monocular camera. The depth prediction model proposed in this research is designed to infer depth information from low-resolution RGB images using an autoencoder architecture.…”
Section: Spatial Representations In 3d and Depth Completion Methodsmentioning
confidence: 99%
“…Examples of research in applying transfer learning to the more specific context of precision forestry applications, to our knowledge, are relatively few. Niu et al [190] employed transfer learning to train their model (see Section 4.1.2) on both indoor and outdoor datasets, including the real-world low-viewpoint forest dataset collected by the authors, described in Section 4.1.5. Andrada et al [157] showed that transfer learning techniques, such as weight initialization with class imbalance (with the "Humans" and "Animals" as the underrepresented classes; see the previous section, Figure 9) and pretrained weights, improved the overall quality of semantic segmentation.…”
Section: Data Augmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Where Wang et al [11] and Fortin et al [5] will focus on detecting only the trunk of the tree, Russell [8] will identify tree tops in aerial views. Viewpoints also differ according to the robots used for application: drones [12] or Unmanned Ground Vehicles (UGV) [13], [14], to name but a few. The diversity of approaches is also reflected in the sensors used.…”
Section: Related Workmentioning
confidence: 99%